Predicting Polymerase Chain Reaction Success: Integrating the K-Word Order Model, Physicochemical Properties Modeling of Double Bases, and Support Vector Machine - Yan, Long; Liu, Yong; Yang, Yan (Combinatorial Chemistry & High Throughput Screening, 2025)
<span class=
Keywords: double bases